(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Land plant Hordeum vulgare L. were produced for the phytoremediation treatment in the variety 0(Control), 5, 10,20,40,80 percent sewage effluent. Maximum values in Hordeum vulgare L. were noticed at 40 effluent for the fresh matter production and dry matter production of 45 days growth. In the end it was observed that the land plants are pretty useful as the phytoremediation treatment of sewage effluent in diluted form as irrigation.